Single institutional study on tubeless percutaneous nephrolithotomy - Sengamuthu, Arun; Sharma, A. K.; Mehendale, Alap Vinay (International Surgery Journal, 2022)
Background: The occurrence of renal stone is increasing which affect 10% of population with recurrence being 70% in affected patients. Tubeless PCNL is the mainstay of treatment in the management of large and complex stones. This study was conducted to evaluate the efficacy, feasibility and safety of tubeless PCNL. Methods: This study was conducted in the department of general surgery, Jagjivan Ram Railway Hospital, Mumbai over a period of one year from March 2019-Febuarary 2020. During this period 50 patients underwent tubeless PCNL for renal stones. Results: Among 50 patients 56% were in the age group of 46-60 years. Most common presenting complaint being flank pain (94%). About 86% of patient had complete stone clearance following tubeless PCNL. Post operative blood transfusion required in 10% of patients. The mean hospital stay was 2.12 days. Most common post operative complication were fever. Conclusions: Tubeless PCNL is a very safe and effective treatment for renal stones.